2018
DOI: 10.1016/j.ejso.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Number of lymph nodes assessed has no prognostic impact in node-negative rectal cancers after neoadjuvant therapy. Results of the “Italian Society of Surgical Oncology (S.I.C.O.) Colorectal Cancer Network” (SICO-CCN) multicentre collaborative study

Abstract: Complete absence of nodes assessed was associated with worse prognosis compared to node-negative and node-positive patients. In node-negative patients number of nodes was not associated to OS and CIDD. Based on data from this large population of irradiated RC, number of nodes assessed has no prognostic impact in node-negative patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…Given the decreased LNY after neo‐CRT, Degiuli et al focused on clinical significance of the complete absence of LNs harvested (ypNnull). Interestingly, ypNnull patients exhibited the worst prognosis comparing to both ypN0 and ypN + patients, which was contrary to several other articles …”
Section: Discussionmentioning
confidence: 99%
“…Given the decreased LNY after neo‐CRT, Degiuli et al focused on clinical significance of the complete absence of LNs harvested (ypNnull). Interestingly, ypNnull patients exhibited the worst prognosis comparing to both ypN0 and ypN + patients, which was contrary to several other articles …”
Section: Discussionmentioning
confidence: 99%
“…Fourth, there is a possibility that individual differences in the number of LNs are related to prognosis. Fifth, large amounts of perigastric lymphoid tissue may be linked to increased barriers to defense against metastasis and robust tumor immunity [15,16]. We believe that our findings of a relative and significant increase in the prevalence of nodal occurrence in the RLN < 40 group are not surprising.…”
Section: Discussionmentioning
confidence: 67%
“…The number of RNLs serves as a prognostic factor for gastric cancer as well as for postoperative survival from certain cancers [9,15,19,20]. For example, for colorectal cancer, > 12 RLNs are recommended; and in the absence of ≥ 12 evaluated nodes, patients should be treated with adjuvant chemotherapy [16]. Moreover, an increase in the number of RLNs is associated with longer survival of patients with node-positive cervical cancer [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the authors included a large number of rectal cancer patients, no subgroup analysis was performed. Studies have shown that a lower LN retrieval in patients with good tumour regression grade or node‐negative disease following neoadjuvant chemoradiotherapy is associated with improved, or does not affect, survival. In these groups of patients, low LN retrieval is an indicator for a good tissue response to neoadjuvant chemoradiotherapy rather than inadequate surgery.…”
mentioning
confidence: 99%